Coriolanus - Shakespeare, William; Edited by Andrews, John F.; Foreword by Dance, Charles (London Everyman, 1998)
This generously annotated edition of Coriolanus offers a thorough reconsideration of Shakespeare's remarkable, and probably his last, tragedy. A substantial introduction situates the play within its contemporary social and political contexts - dearth, riots, the struggle over authority between James I and his first parliament, the travails of Essex and Ralegh - and pays particular attention to Shakespeare's shaping of his primary source in Plutarch's Lives. It presents a fresh account of how the protagonist's personal tragedy evolves within Shakespeare's most searching exploration of the political life of a community." "The edition is alert throughout to the play's theatrical potential, while the stage history also attends to the politics of performance from the 1680s to the 1990s, including European productions following the Second World War.
Keywords: Coriolanus, Cnaeus Marcius -- Rome (Empire) -- Generals